Bali Strait‘s Potential Fishing Zone of Sardinella lemuru - Dinarika Jatisworo; Bambang Sukresno; Denny Wijaya Kusuma; Eko Susilo (Faculty of Geography, Universitas Gadjah Mada, 2022)
Catch fluctuation of Sardinella lemuru in the Bali Strait in the period 2007 - 2019 shows a significant decrease. The fishermen of this area demanded information on the Potential Fishing Zone (PFZ) specifically targeted for Sardinella lemuru beyond their traditional. PFZ will be very helpful, especially during the famine years. Identification of a Potential Fishing Zone (PFZ) is highly important for increased fishing yields and also reduced fishing time for fishermen. Bali strait is dominated by Sardinella lemuru and contributes 16,2% of the total small pelagic fishery production in Fisheries Management Area (FMA) 573. Bali Strait also supports the fishing industry in Muncar (Banyuwangi-East Java) and Pengambengan (Jembrana-Bali). This study will produce a special PFZ for Sardinella lemuru that is not yet available in Indonesia by using remotely sensed and observer data. Here, we apply the Empirical Cumulative Distribution Function (ECDF) algorithm approach for Sardinella lemuru detection. ECDF was developed using Sea Surface Temperature (SST) and Chlorophyll-a (Chl-a) data from Aqua MODIS and extracted according to observer data during 2011-2014. PFZ for Sardinella lemuru in Bali strait was affected by 72,8 % Chl-a conditions and 27,2% by SST conditions. The maximum suitable preference for Sardinella lemuru in Bali Strait is Chl-a condition at 0,2 mg/m3 and SST condition at 28,38°C in northwest monsoon, while in southeast monsoon are 0,97 mg/m3 for Chl-a and 25,61°C for SST. ECDF model result has 69,33% accuracy, which shows the result of Sardinella lemuru PFZ has good accuracy.